2012
DOI: 10.1051/0004-6361/201117705
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic outflow drivesγ-ray emission in 3C 345

Abstract: Aims. On the basis of the first 20 months of Fermi-LAT data and optical monitoring, the quasar 3C 345 has been identified as a γ-ray emitter. We investigate whether there is a connection between the γ-ray and optical variability of 3C 345 and the properties of its parsec-scale radio emission. Methods. We combined the Fermi-LAT data of 3C 345, covering an energy range of 0.1-300 GeV, with 32 Very Long Baseline Array observations of the object made at 43.2 GHz in the period of January 2008-March 2010.Results. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 46 publications
4
101
0
Order By: Relevance
“…To derive the kinematics of the source, we fit polynomials to the observed x-and y-positions of the fitted components. We follow the procedure presented in e.g., Homan et al (2001) and Schinzel et al (2012), using firstand second-order polynomials if the components was detected in more than ten epochs (the latter can only be applied to the long-term monitoring of the source at 15 GHz and 43 GHz):…”
Section: Calculation Of Kinematic Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…To derive the kinematics of the source, we fit polynomials to the observed x-and y-positions of the fitted components. We follow the procedure presented in e.g., Homan et al (2001) and Schinzel et al (2012), using firstand second-order polynomials if the components was detected in more than ten epochs (the latter can only be applied to the long-term monitoring of the source at 15 GHz and 43 GHz):…”
Section: Calculation Of Kinematic Parametersmentioning
confidence: 99%
“…These observations provide a tool to test several jet models and to probe how variations within the first few parsecs contribute to the high-energy emission. The brightness temperature, T b , can be used to derive estimates of the dominant energyloss mechanism and the evolution of intrinsic properties, such as the jet speed, the particle density, and the magnetic field (e.g., Kadler et al 2004;Schinzel et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Kovalev et al 2009;Pushkarev et al 2010;Leon-Ravares et al 2011;Schinzel et al 2012;Wehrle et al 2012;Kutkin et al 2014). In this scenarios, we could determine the properties of jet through observing the electromagnetic spectrum.…”
Section: Introductionmentioning
confidence: 97%
“…We further discuss studies of the γ-ray production beyond the radio core. Schinzel et al (2012) found from the VLBA, optical and γ-ray monitoring of the quasar 3C 345 that γ-ray emission from 0.1-300 GeV is driven by relativistic outflows of the jet and is produced in a region of the jet that extends up to ∼ 23 pc. The γ-ray emission is proposed to arise from SSC.…”
Section: Location Of γ-Ray Emission In the Jetmentioning
confidence: 99%
“…Series of quasi-stationary knots and knots moving downstream the jet are often identified from the VLBA monitoring of blazars. The first stationary component from the radio core is located at submilliarcsecond scales which translates to a sub-parsec distance for nearby RGs 3C 390.3, 3C 120, BL Lacertae and M 87, and FSRQs 3C 273 and 3C 345.3 (e.g., Arshakian et al 2010;León-Tavares et al 2010;Cohen et al 2014;Cheung et al 2007;Jorstad et al 2005;Schinzel et al 2012). This stationary component appears to be a common feature in blazars and it is likely to be a standing recollimation shock (RCS), which is evident from HD/MHD simulations of jets (e.g., Gomez et al 1995;Krause & Gamenzid 2001).…”
mentioning
confidence: 99%